Educational Environment - Troncon, Luiz Ernesto de Almeida (Medicina (Ribeirao Preto), 2014)
The educational environment is composed by a number of factors that influence learning and affect academic performance and student satisfaction. The components of the educational environment are related to student physiological needs and emotional responses. The educational environment is determined by the school and the teacher, but student also plays a role in its maintenance and improvement. A variety of instruments have been described for the evaluation of the educational environment, which could be understood as a process of collecting data that should inform decision making processes aiming at improving educational environment. This will result in increased quality of student learning and development.